ETNOEKOLOGI MASYARAKAT NELAYAN DALAM PELESTARIAN DANAU BUYAN - Juliasih, Ni Ketut Ayu; Suyasa, I Wayan Budiarsa; Suarna, I Wayan; Sudarma, I Made; Suyoga, I Putu Gede; Ni Luh Gede Sudaryati (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2024)
This study examines the ethnoecology of fishing communities in the conservation of Lake Buyan,with an analytical focus on the cosmos system, Corvus and daily praxis. This study uses aqualitative descriptive analytical method with a basis for data analysis based on cultural ecologytheory and generative structuralism. Fisherman behaviour data was obtained from distributingquestionnaires using analysis referring to the binary model. This study, which was conducted inMay - August 2023, found that the cosmos system or belief in a divine nature and strong magicalmystical beliefs collaborate to form and strengthen cultural capital, social capital and symbolic capital as one unit with rational and irrational knowledge forming a complex system. Corvus. This conception complements the individual and collective habitus of fishing communities throughconventions as values, norms and rules that are adhered to physically and mentally. The localwisdom of the fishing community underlies every daily practice. Both in understanding andutilizing Lake Buyan in its functions as a source of drinking water, agriculture, socio-cultural/religious, economic, recreation or tourism, and ecology. This praxis is also reflected in the resultsof fishermen's behaviour which is included in the good category with a score of 1.